Ruch graniczny z Polski do Obwodu Kaliningradzkiego na tle pozostałych odcinków zewnętrznej granicy Unii Europejskiej: Border traffic from Poland to the Kaliningrad region in the context of other sections of the external border of the European Union - Rosik, Piotr; Wiśniewski, Rafał (Przegląd Wschodnioeuropejski, 2021)
The purpose of the paper is to present the cross-border mobility of Poles in a broader context of social, economic changes and formal and political conditions. The mobility of Poles is presented on the example of border traffic on the Polish-Russian border. We compare the situation on the border with Kaliningrad oblast with other sections of the eastern border. We focus on number of crossings and the movement of passenger and heavy good vehicles based on the data of the Border Guard. The conclusions are as follows: the intensity of border traffic was conditioned by both formal and legal changes as well as the economic situation on both sides of the state border. In the period from 1990, intensive travels of Poles to the Kaliningrad oblast were carried out: (1) from the mid-1990s until Poland’s accession to the European Union; (2) during the operation of local border traffic, i.e. in the years 2012-2016.